Green synthesis of cyclohexanone to adipic acid over Fe-W oxides incorporated mesoporous carbon support - Mekala, Siva Prasad; Prabu, Marimuthu; Gawali, Sheetal Datta; Gopakumar, Karthik; Gogoi, Pranjal; Bhatkar, Akash Ravindra; Mohapatra, Gourab; Unnikrishanan, Eeswar; Raja, Thirumalaiswamy (Catalysis Communications, 2022)
We have prepared iron and tungsten oxides incorporated mesoporous carbon (MC) catalysts using a simple hydrothermal methodology with different carbon sources, and the catalytic performance was investigated for cyclohexanone oxidation. An adequate amount of metal oxide loading has displayed a key role in the selective catalyst for adipic acid (AA) synthesis. The MC catalyst has shown its prime activity under the influence of redox properties of W5+/W6+ and Fe2+/Fe3+ as promoters. The 10%Fe 90%W-MC fructose as a carbon source catalyst has provided its best selectivity of 87% for AA at 120 ?C.
Keywords: Adipic Acid; Liquid phase oxidation; mesoporous carbon; Redox center